The agricultural education outreach project in Aklan Barangay Sibalew, Banga. - Bautista, Reynold R.
This study uses the concept of agricultural extension as a catalyst of cahnge for rural development. Suffice it to say, the objective of agricultural extension is to provide the rural people the appropriaate information, technology and values to make them self-reliant in the context of their own environment. However the realization of this goal is dependent on the extent of acceptance and participation of the rural people themselves. In this study, the Aklan Agriculture College-Agricultural Education Outreach Project in Aklan is supposed to bring self-reliance among the farmers of barangay Sibalew, Banga by effective transfer of appropriate-technology. Basing on the principles of extension service, it has been determined that the A.E.O.P project in Sibalew, particularly its economic and social services, has been instrumental in improving the productivity and income and broadly, the social and economic aspects of the farmers' kife. Needless to say, the A.E.O.P-introduced technologies have been embraced by themajority of farmers in the barangay--which exemplifies the effectiveness of the A.E.O.P project.